STRATEGI PEMBELAJARAN REMEDIAL DAN IMPLEMENTASINYA DALAM PEMBELAJARAN - Karyanto, Umum B. (Forum Tarbiyah, 2011)
Abstract: Students often gripe about remediation, as if the remedialprograms becomes a frightening specter for students. Manycontributing factors of why students often do remedial, among othersis the lack of prerequisite knowledge, it is difficult to understand thematerial of Competence Standard / Basic Competence granted. Even,among us, it is also still the lack of understanding about the remediallearning. Before giving remedial learning, at first, educators need toimplement the diagnosis of learners with learning difficulties by usingtest, interviews, observations, and so on. Having in mind the difficultyof learning, learners are given remedial teaching. Many techniquescan be used, e.g. are learning with different methods and media,simplification of the material, the use of peer tutors, and so on. Todetermine the mastery level after taking remedial learners, re-test isneeded, while the results must not exceed the minimum score ofminimal completeness criteria (KKM).